Selectorless Oxide-Based Resistive Switching Memory with Nonuniform Dielectric for Low Power Crossbar Array Applications. (23rd April 2019) - Chen, Ying-Chen; Lin, Chao-Cheng; Kim, Sungjun; Lee, Jack C.
Abstract : Selectorless resistive random-access memory (RRAM) with self-rectifying behavior is presented as a way to suppress sneak path current without an additional transistor or switch device integration, which is beneficial for reducing the cost and complexity of crossbar array fabrication. In this work, selectorless 1R-only graphite-based memristor devices have been demonstrated by utilizing the nonlinear (NL) resistive switching (RS) characteristics with well-designed operation conditions. The early stage of cycling observation as seasoning effect is investigated, while the wear-out mechanism is also discussed for the selectorless 1R-only RRAM crossbar array for high storage class memory applications.